Leadership lessons from the Kardashians : bodies, emotions, success - Biehl, Brigitte (Emerald Publishing Limited, 2024)
The Kardashians are not only a massive global pop culture phenomenon, they are also effective business leaders and entrepreneurs having established many brands and companies. In addition to their celebrity, they successfully market their businesses and serve as aspirational role models. They have changed our understanding of what successful women in the economic arena look like and how they're supposed to behave. Brigitte Biehl uses examples from the popular TV series "The Kardashians" and "Keeping up with the Kardashians" to explore leadership concepts that focus on women in business, and the obstacles they face in a male dominated world. Among the many subjects that will appeal to a variety of readers, from college students to professional practitioners, Biehl addresses questions of gender performativity, bodies, motherhood, race, class, as well as issues on female misogyny and masculine leadership stereotypes. The book provides guidelines how to use TV series and film for self-directed learning to develop a better awareness and understanding of what goes on between people and one's own leader identity. Exploring Effective Leadership Practices through Popular Culture aims to bring examples, theory and methodology of leadership to life by analyzing academic concepts through popular culture examples that will appeal to a broad range of readers.
Keywords: Kardashian family.; Family-owned business enterprises.; Leadership.; Women-owned business enterprises.; Business & Economics -- Leadership.; Family and Owner-Managed Companies.; Management: leadership and motivation.; elektronické knihy; electronic books